(untitled) (Tzintzun, Revista de Estudios Históricos, 2023)
The objective of this article is to analyze the case of the medicine in Mexico at the beginning of the 20th century known as Zendejas Specific, its main characteristics, as well as the legal disputes and controversies that took place regarding its distribution and commercialization. The study shows the transformation of the Mexican pharmacy that occurred during these decades, characterized by the adoption of industrial medicine and the abandonment of the use of medicinal plants, as well as by the implementation of pharmaceutical legislation based on modern scientific principles.